Pengembangan Sistem Informasi Manajemen Pengelolaan Member Fitness dan Kebutuhan Nutrisi Member serta Pemantauan Perkembangan Usaha berbasis Website (Studi Kasus: Executive Gym, Kota Cilegon) - Rizky Ramadhana; Fajar Pradana; Achmad Arwan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Fitness can make the body fitter and look good by lifting weights, no wonder fitness centers are increasingly popular with the community, one of which is the Executive Gym. However, it is difficult for Executive Gym owners to monitor the running of the business in real time. Lack of monitoring means that information on business developments cannot be obtained quickly and accurately. From the receptionist side, all recording was done in handwriting which tended to take longer and was complicated so it was not effective and efficient. At the time of training, the instructor had difficulty knowing the exact amount of nutrition the members needed, so the instructor still relied on estimates and this became a concern as well. So, the Development of Information System Management for Fitness Member and Member Nutritional Needs and Business Growth Monitoring Website-Based with the Executive Gym case study was carried out , so that the receptionist can manage visitors effectively and efficiently. Business owners can monitor the running of the business in real time from afar and get the necessary reports in detail for a business development strategy. In addition, the instructor can calculate the nutritional needs as well as the amount of food that the member needs appropriately. Development is carried out using the waterfall model. The system was tested by unit testing, integration testing, and validation testing of 49 test cases with a valid value of 100%, and usability testing with a result of 91% (very feasible) and a Cronbach alpha value of 0.98 (perfect).